Commerce and Sentiment in Tales of Barbary Encounter: Cathcart, Barlow, Markoe, Tyler, and Rowson - Andrew S. Gross (European Journal of American Studies)
A number of American sailors were taken hostage by Barbary Corsairs and held as slaves in North Africa in the years following the Revolutionary War.  The crisis would ultimately lead to open warfare, but many Americans were optimistic that international commerce and common sympathy might overcome religious differences.  This essay sketches the history of the Barbary conflict and considers three fictionalized accounts of Barbary encounter as secular conversion narratives, two of the three demonstrating how even despotic slaveholders could learn to embrace commerce and sentiment.  Peter Markoe’s novel The Algerine Spy in Pennsylvania (1787), Royall Tyler’s The Algerine Slave (1797), and Susanna Rowson’s drama Slaves in Algiers (1794) suggest a certain openness to religious and national difference; however they are clearly about American concerns and, in fact, more committed to secularized Christian norms than their praise of common sentiment would suggest.  In all three texts, Jews are excluded from the vision of common sentiment and made to symbolize what was cruel about commerce; it is my argument that they served as scapegoats for the American discomfort with its own failures of sentiment, evidenced most obviously by chattel slavery and the slave trade.  These fictionalized tales of encounter hold up sentiment as the solution to all sorts of conflict.  However, they also deploy sentiment, paradoxically, as a pre-biological marker of race, designating those beyond the union of sentiment—Jews—as somehow detached from the quality that makes people human.